Hak Syuf’ah Menurut Fikih Muamalah dan Serapannya dalam Kompilasi Hukum Ekonomi Syariah: The Rights of Syuf'ah According to Fiqh Muamalah and Its Absorption in the Compilation of Sharia Economic Law - Nur Zaki, Fakhri; Jahada Mangka; Sirajuddin, Sirajuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the rights of syuf'ah according to the perspective of fiqh muamalah and its absorption in the Compilation of Islamic Economic Law (KHES) with the research method used is descriptive qualitative (non-statistical) using the library research method and the Juridical Normative approach. and Statue Approach. The results of this study found that the right of syuf'ah in general is the right of partners/partners (syafī') to forcibly take over what has been sold by their union partners in the form of immovable property or assets to third parties or new buyers by paying compensation. or costs in accordance with those incurred by the third party or the new buyer. Meanwhile, according to the Sharia Economic Law Compilation in general, syuf'ah rights are the rights of a legal object over another legal subject to take precedence in the transfer or transfer of ownership of an immovable object as a substitute for sulh. So far the guidelines mentioned in the KHES regarding syuf'ah rights are still limited to mentioning definitions, wisdom and a small part of the provisions of syuf'ah rights that exist in muamalah fiqh. There are still many other provisions of syuf'ah rights in muamalahfiqh that have not been absorbed (adopted) in KHES such as the provisions regarding Masyfū 'alaih which is one of the main topics of syuf'ah rights.